(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
A CT scan depends on taking many X-ray images at the same time, with the aim of imaging the body and organ in the form of thin slices. By merging these images together, the internal structure of each organ appears very accurately, even the smallest changes present. The CT scan image is formed in three dimensions by merging the images. From different angles, a dye containing iodine or barium can be used in a CT scan, and it is injected through the peripheral veins in order to clearly show the wall of the internal blood vessels. It is called a CT scan. The difference between the development of magnetic resonance imaging (MR) and computed tomography (CT) is that the CT scan is It is faster than MRI, and is also cheaper than MRI, and less sensitive to patient movement, unlike MRI, and CT imaging is safe for patients who suffer from fear of closed spaces. CT imaging can be performed using implantable medical devices such as pacemakers or magnetic vascular clips